STRATEGI MEDIA RELATIONS TIM SUKSES CALON PRESIDEN-WAKIL PRESIDEN MELALUI MEDIA SURAT KABAR DAERAH - Yuniarti, Tatik (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2010)
In political developments, the press is often a tool used by political elites for their sake of party and political propaganda. This is because the mass media has the power to influence society in a choice pair of presidential and vice presidential candidate. The aim of this research is to find out how the winning strategies used by success team of presidential and vice presidential candidate. The research uses content analysis method. From the analysis conducted, it is obtained that the success team of president and vice presidential candidate tend to be not optimally utilize the news media as connective information to the public. That's what ultimately realized by the success team of Wiranto-Salahuddin Wahid and Amin Rais-Siswono Yudo Husodo presidential and vice presidential candidate as one of the factors that affects both of them were lost in the 2004 presidential election. But the mass media control is not necessarily used as a benchmark victory presidential and vice presidential candidate, because the factors that influence the victory of the presidential election must also consider the respective candidates support base.